INTERRELATION BETWEEN PLASTIC VISCOSITY OF CEMENT SYSTEMS AND THEIR RETHEHNOLOGICAL CHARACTERISTICS - Sh. M. Rakhimbayev; N. M. Tolypina; E. N. Khakhaleva (Вестник СибАДИ)
Introduction. The theoretical basis for regulating the mobility and workability of concrete mixtures and other rheologically complex bodies is rheology. The authors give a clarification of the physical meaning of the terms plasticizer, superplasticizer, diluent of cement systems.Materials and methods. In the construction industry, suspensions and pastes are widely used to characterize the rheological properties of the cone spill, which does not always ensure the adequacy of their mobility. It has been found that the relationship between the plastic viscosity and the expansion of the cone depends on the degree of dilution of their modifying additives.Results. It is shown that the value of cone expansion, especially in the field of moderate doses of additives, adequately reflects the rheological properties of cement systems. With large and small values of plastic viscosity, the cone decay weakly reflects the rheological properties of disperse systems.Discussion and conclusions. Recommendations on the rational use of rasplav cone to characterize the technological properties of cement systems are given in the article.